Body image dissatisfaction and dietary patterns according to nutritional status in adolescents - Rita de Cássia Ribeiro-Silva; Rosemeire Leovigildo Fiaccone; Maria Ester Pereira da Conceição-Machado; Ana Santos Ruiz; Maurício Lima Barreto; Mônica Leila Portela Santana
Abstract Objective There is a lack of data on the association between body self-perception and eating patterns in Brazil. Thus, this study aimed to explore the relationship between body image dissatisfaction and eating patterns by the anthropometric status in adolescents. Methods A cross-sectional study of 1496 adolescents was conducted. The participants completed the Body Shape Questionnaire. Demographic, anthropometric, and socioeconomic data were collected, as well as information regarding the pubertal development and dietary intake. Logistic regression was performed to evaluate the associations of interest. Results Body image dissatisfaction was identified in 19.5% of the adolescents. Three dietary patterns were identified: (1) the Western pattern was composed of sweets and sugars, soft drinks, typical dishes, pastries, fast food, beef, milk, and dairy products; (2) the Traditional pattern was composed of oils, chicken, fish, eggs, processed meat products, cereals (rice, cassava flour, pasta, etc.), baked beans, and bread; and (3) the Restrictive pattern was composed of granola, roots, vegetables, and fruit. Among overweight/obese adolescents, the data indicated a negative association of slight body image dissatisfaction (OR: 0.240 [0.100; 0.576]) and moderate body image dissatisfaction (OR: 0.235 [0.086; 0.645]) with the Western dietary pattern. Additionally, in this group, there was a positive association between high body image dissatisfaction and the Restrictive pattern (OR: 2.794 [1.178; 6.630]). Conclusion Amongst overweight/obese adolescents, those with slight and moderate body image dissatisfaction were less likely to follow a Western-like dietary pattern when compared with those satisfied with their body image. Additionally, in this group, adolescents with high body image dissatisfaction was more likely to follow a restrictive pattern.